Cost and outcomes of the ultrasound screening program for birth defects over time: a population-based study in France. Issue 7 (20th July 2020) - Ferrier, Clément; Khoshnood, Babak; Dhombres, Ferdinand; Randrianaivo, Hanitra; Perthus, Isabelle; Jouannic, Jean-Marie; Durand-Zaleski, Isabelle
Abstract : Objective: To assess trends in the average costs and effectiveness of the French ultrasound screening programme for birth defects. Design: A population-based study. Setting: National Public Health Insurance claim database. Participants: All pregnant women in the 'Echantillon Généraliste des Bénéficiaires', a permanent representative sample of 1/97 of the individuals covered by the French Health Insurance System. Main outcomes measures: Trends in the costs and in the average cost-effectiveness ratio (ACER) of the screening programme (in € per case detected antenatally), per year, between 2006 and 2014. incremental cost-effectiveness ratio (ICER) from 1 year to another were also estimated. We assessed costs related to the ultrasound screening programme of birth defects excluding the specific screening of Down's syndrome. The outcome for effectiveness was the prenatal detection rate of birth defects, assessed in a previous study. Linear and logistic regressions were used to analyse time trends. Results: During the study period, there was a slight decrease in prenatal detection rates (from 58.2% in 2006 to 55.2% in 2014; p=0.015). The cost of ultrasound screening increased from €168 in 2006 to €258 per pregnancy in 2014 (p=0.001). We found a 61% increase in the ACER for ultrasound screening during the study period. ACERs increased from €9050 per case detected in 2006 to €14 580 per case detected in 2014 (p=0.001). ICERs had an erratic pattern, with a strong tendency to show that any increment in the cost of screening was highly cost ineffective. Conclusion: Even if the increase in costs may be partly justified, we observed a diminishing returns for costs associated with the prenatal ultrasound screening of birth defects, in France, between 2006 and 2014.